Analisis Permainan Tradisonal Tenggedi Bu’au Diera Digital Anak Usia Dini - Asya Angraini Langindara; Adita Putri Rauf; Anisa Putri Rahim; Putri Desriyanti Ahmad (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
Tenggedi Bu’au, a traditional game originating from Gorontalo, represents an important element of the region’s cultural heritage, embodying values such as agility, sportsmanship, discipline, and emotional self-control. Despite its cultural significance, the popularity of Tenggedi Bu’au has declined in the digital era, as younger generations tend to prefer technology-based games that offer instant entertainment. This paper aims to analyze the current existence of Tenggedi Bu’au, its cultural meaning, and the challenges and opportunities for preserving it in a rapidly digitalized society. Through a literature-based analysis, the study highlights that Tenggedi Bu’au remains relevant as a medium for character education, cultural strengthening, and the development of social interaction skills. The game also holds potential to be revitalized through creative approaches, such as digital animation, interactive learning media, cultural festivals, and school-based educational programs. Furthermore, the study emphasizes that strategic collaboration among local communities, cultural practitioners, educational institutions, and government stakeholders is crucial to ensure the long-term sustainability of this traditional game. By integrating traditional values with modern innovation, Tenggedi Bu’au can continue to be appreciated by younger generations while maintaining its role as a symbol of Gorontalo’s cultural identity.